STALLING LIMIT KOMPRESSOR STATOR KASKADE DENGAN BRITISH PROFIL 9C7/32,5 C50 PADA STAGGER 40 - Marsan, Kennedy (MEKTEK, 2007)
Stalling condition of stator cascade compressor using British Profile 9C7 / 32,5. C50 at stagger angle 40, has reach at angle of attack 16O, although the value of turning angles (12) and losses tend to stabilize. This matter because of the blockage effect on the blade corner, shares stream to concentration to the middle O, this phenomena causing the cascade cannot rising the pressure more. The stalling condition at stagger 40 dominated by the corner stall phenomenon